PEMANFAATAN AMPAS KOPI ROBUSTA DALAM PRODUK BAKERY: KAJIAN AKTIVITAS ANTIOKSIDAN, SERAT, DAN SIFAT FISIKOKIMIA - Hafiz Al Muwaththa (Jurnal Agroindustri Pangan, 2026)
The global coffee industry generates spent coffee grounds (SCG) waste exceeding 50% of coffee cherry mass at each processing stage. Annual SCG production reaches millions of tons, causing environmental pollution through anaerobic decomposition that releases greenhouse gases. However, SCG contains valuable components, including 66% dietary fiber on a dry basis, Total Phenolic Content (TPC) of 21.6 mg GAE/g, and bioactive compounds such as caffeine and chlorogenic acid These constituents support SCG classification as antioxidant dietary fiber with potential to control oxidative stress. SCG utilization in bakery products has proven to enhance nutritional value and antioxidant activity. Substitution of 4–7% SCG in cookies increased TPC and dietary fiber without compromising sensory acceptance, while 10% substitution in shortbread significantly improved protein, fiber, and antioxidant activity. Application in gluten-free products also demonstrated increased phenolic content and antioxidant capacity. This review aims to analyze SCG potential as a functional ingredient in bakery products, covering antioxidant activity profiles, dietary fiber characteristics, and physicochemical property modifications. Results indicate optimal substitution ranges from 2–10% depending on product type, with significant improvements in nutritional value, biological activity, and product stability. SCG utilization supports sustainable food development while reducing agro-industrial waste